2012
DOI: 10.1111/j.1745-4549.2012.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

THEIN VITROFREE RADICAL-SCAVENGING AND ANTIFUNGAL ACTIVITIES OF THE MEDICINAL HERBLIMONIUM ECHIOIDESL. GROWING WILD IN TUNISIA

Abstract: The petroleum ether, chloroformic, ethyl acetate and methanolic extracts of Limonium echioides L. (Plumbaginaceae) were screened for their antioxidant and antifungal activities through in vitro experiments. The 2,2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid) diammonium salt (ABTS•+) decolorization and 1,1‐diphenyl‐2‐picrylhydrazyl (DPPH•) free radical‐scavenging method were used. All extracts were active with radical‐scavenging capacity reaching 100% in DPPH• reaction system and 85.6% in ABTS•+ reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…Radcl.-Sm. [47], L. echioides [48], L. densiflorum [37], L. delicatulum [36], L. myrianthum, L. leptophyllum and L. gmelinii [49], but not for L. binervosum, so direct efficacy comparisons are not possible.…”
Section: Antimicrobial Activity Of Limonium Spp Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radcl.-Sm. [47], L. echioides [48], L. densiflorum [37], L. delicatulum [36], L. myrianthum, L. leptophyllum and L. gmelinii [49], but not for L. binervosum, so direct efficacy comparisons are not possible.…”
Section: Antimicrobial Activity Of Limonium Spp Extractsmentioning
confidence: 99%
“…Concerning the antifungal activity of Limonium spp., a low antifungal activity was reported for L. echioides (against Fusarium oxysporum and Penicillium sp. [48]), for L. avei (against Candida albicans [46]), and for L. densiflorum and L. delicatilum (against Candida spp. [36,37]).…”
Section: Antimicrobial Activity Of Limonium Spp Extractsmentioning
confidence: 99%
“…Halophytes Limonium spp. (Plumbaginaceae, sea lavenders) are found in coastal areas all over the world (Kubitzki, 1993) and produce metabolites with diverse bioactivities (Lee et al, 2011;Saidana et al, 2013). Limonium algarvense Erben is an Iberian-Moroccan endemism (Caperta et al, 2017) valued source of antioxidants with potential applications in the agro-food industry (Rodrigues et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are in agreement with the literature. In fact, several Limonium species are known to be rich in tannins Siddhuraju et al . reported that a high concentration of tannins increased the free radical DPPH scavenging capacity.…”
Section: Discussionmentioning
confidence: 99%